Necesidad de establecer reformas legales en el art. 1.- de la Ley Del Anciano por cuanto ocasiona violación de sus derechos en la relación a la norma constitucional contenida en el artículo 37, numeral 2 de la Constitución de la república del Ecuador - Quevedo Arias, Carlos Manuel (2016)
The present titled investigation work: ""NECESSITY TO ESTABLISH LEGAL REFORMATIONS IN THE ART. 1 OF THE OLD MAN'S LAW SINCE IT CAUSES VIOLATION OF THEIR RIGHTS IN THE RELATIONSHIP TO THE CONTAINED CONSTITUTIONAL NORM IN THE ART. 37, NUMERAL 2 OF THE CONSTITUTION OF THE REPUBLIC OF THE EQUATOR." The investigation was developed on the base in the empiric and theoretical so much scientific methods with the purpose of detecting the violations that the employers make private publics so much, with the purpose of strengthening of the labor process to promote a better level of life in the old men, leaning on in the recovery and systematizing of relating theoretical, diagnostic of causes and consequences and the elaboration and execution of the proposal. In the development of the present investigative work it was gathered all the information necessary point of the employers and employees, through surveys, interviews and observation, data that after being processed and examined they established that the economic problems and the discrimination of the age affect the rights notably in relation to the constitutional norm contained in the article 37, numeral 2 of the constitution of the republic of the Ecuador